Tax Planning and Business Entity Market Value: Insights from the Mining Sector in Indonesia - Berwin Anggara (AKUNTANSI 45, 2025)
This research endeavors to scrutinize the implication of tax planning strategies upon firm valuation within the mining sector enterprises listed on the Indonesia Stock Exchange throughout the observational period of 2018–2022. The study addresses the challenges precipitated by commodity price volatility and stringent fiscal regulations, particularly the Tax Regulation Harmonization Law of 2021, which profoundly impacts cash flow dynamics and investment attractiveness. The research methodology employs multiple linear regression analysis on a stratified sample of 28 corporations drawn from a comprehensive population of 62 entities, utilizing secondary data procured from annual financial statements accessed through www.idx.co.id. The independent variables encompassing tax planning efficacy are quantified through the Effective Tax Rate (ETR) and Tax Retention Rate (TRR), while firm valuation is assessed via the Price-to-Book Value (PBV) metric. The analytical findings demonstrate that ETR exerts a statistically significant negative influence upon PBV (p=0.016), whereas TRR exhibits no significant impact (p=0.541). Concurrently, ETR and TRR collectively influence PBV with statistical significance (p=0.001) and substantial explanatory power (R²=0.837). These empirical discoveries substantiate signalling theory, wherein efficient tax planning strategies function as positive market signals to investors, while simultaneously underscoring the critical importance of aggressive tax optimization approaches for enhancing market valuation within high-risk sectoral contexts. This research furnishes significant implications for regulatory authorities in fiscal oversight mechanisms and for corporate entities in post-pandemic financial optimization endeavors.